The WTO Transit Regime for Landlocked Countries and its Impacts on Members’ Regional Transit Agreements The Case of Afghanistan’s Transit Trade with Pakistan - Akbari, Suhailah (EYIEL Monographs - Studies in European and International Economic Law, 2021)
XVIII, 247 p. 1 illus.